Vers une écologie de l’expérimentation « hors norme » des ressources matérielles en architecture - Hector Docarragal Montero; Olivier Jeudy (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The many standards in place in France often appear as an obstacle to environmental transition in architectural projects. The French government has thus expressed desire to implement exemptive measures inside the ESSOC and LCAP laws, which raise questions about the establishment and approach of standards. In the context of this article, we examine whether these laws encourage an ecological approach to architectural materials. We first examine three laureate projects from the competition "Permis d’innover" (LCAP law), which have the particularity of opening up new perspectives for the valorization of architectural materials through an experimental approach that deviates from standards. We then query the efficiency of the use of "non-approved" materials and their capacity to redefine new performance conditions. The government’s interest in these alternative strategies, along with its commitment to support exemptive devices (LCAP and ESSOC laws) reveal the dimension of a new approach for architectural projects which tend to overcome the regulatory framework. At the same time, the capacity of other materials to create new ecological solutions would consolidate this field of experimentation in progress.